On the some properties of the orthogonal polynomials over a contour with general Jacobi weight - Abdullaev, F.G.; Abdullaev, G.A. (Український математичний вісник, 2016)
In present work, we continue the study the growth of the orthogonal polynomials over a contour with weight function in the weighted Lebesgue space, when the contour and the weight function having some singularities. We study case, when interference of weight and contour is not satisfied, for piecewise smooth contour with interior zero angles. Also we investigated case of more general contours.